Determinants of willingness to become organ donors among dialysis patients' family members - Tumin, M.; Satar, N.M.; Zakaria, R.H.; Raja Ariffin, R.N.; Lim, S.K.; Ng, K.P.; Tafran, K. (Urology and Nephrology Research Centre, 2015)
Purpose: This study explores the factors affecting the willingness of dialysis patients' family members to become involved in living and deceased organ donation. Materials and Methods: We utilize cross sectional data on 350 family members of dialysis patients collected through self-administered survey from June to October 2013. The factors affecting willingness to become deceased and living organ donors among respondents were identified by running logistic regressions. Results: The findings reveal that ethnicity, education and role in family are significant factors explaining willingness for living donation, while ethnicity, knowledge of organ donation and donor age drive willingness for deceased donation. We also find that the reasons of respondents being unwilling to donate center on the lack of information and family objections for deceased donation, while being medically unfit, scared of surgery and family objections are the reasons for unwillingness to donate living organs. Conclusion: In light of our findings, educational efforts are suggested to decrease the reluctance to become involved in living and deceased donation.